Solid solutioning in ZrB2 with HfB2: Effect on densification and oxidation resistance. (November 2019) - Hassan, Rubia; Omar, Shobit; Balani, Kantesh
Abstract: Solid solution formation in ZrB2 with HfB2 addition along with SiC reinforcement is investigated. To impart enhanced oxidation protection, solid solution formed is synergistically reinforced with CNTs. With the formation of solid solution, an increase in densification, evaluated using different methods, is reported. Phase analysis shows the peaks of (Zr, Hf)B2 solid solution positioned between the corresponding peaks of ZrB2 and HfB2 . Thus, lattice parameters (calculated by performing Rietveld refinement) were found to lie between the lattice parameters of monolithic ZrB2 (a = b = 3.169 Å, c = 3.530 Å) and HfB2 (a = b = 3.142 Å, c = 3.480 Å), confirming the formation of solid solution. The exothermic peak of ZrB2 oxidation shifted from 732 °C in ZrB2  + SiC composite to 745 °C in (HfB2  + ZrB2 ) + SiC with solid solutioning and further to 812 °C with CNT reinforcement in ZrB2  + (HfB2  + ZrB2 ) + SiC+CNT composite, elucidating an increase in oxidation resistance revealing the potential of these composites for aerospace applications. Graphical abstract: Unlabelled Image Highlights: Spark plasma sintering of ZrB2 -SiC, ZrB2 -HfB2 -SiC, ZrB2 -HfB2 -SiC-CNT composites Solid solution formation in ZrB2 -SiC with HfB2 addition Increase in densification with solid solution formation CNT reinforcement increases the tendency of solid solutioning Improved oxidation resistance with solid solutioning and further with the CNT reinforcement